Water disinfection in the mountains - an update of the recommendation of the Medical Commission of the Union Internationale des Associations d'Alpinisme (UIAA) - C. Albanus; L. Timmermann; V. Schoeffl; D. Hillebrandt; J. Milledge; Thomas Küpper (University of Applied Sciences in Tarnow, Poland, 2021)
Safe water is still a major problem for travellers in many countries worldwide. In the last decade several new technical developments were made and more data exist about traditional procedures to produce safe water. This update includes such data with special regard to UV-C and held devices and SODIS.